Regeneration of rete ridges in Lanyu pig (Sus scrofa): Insights for human skin wound healing. Issue 4 (27th February 2019) - Lin, Chein‐Hong; Chiu, Po‐Yuan; Hsueh, Yuan‐Yu; Shieh, Shyh‐Jou; Wu, Chia‐Ching; Wong, Tak‐Wah; Chuong, Cheng‐Ming; Hughes, Michael W.
Abstract: Rete ridges are important to the mechanical function of skin in animals with minimal hair, including humans. As mice do not exhibit rete ridges, the need for a quality animal model is pertinent. Here, we develop a Lanyu pig ( Sus scrofa ) full‐thickness wound model to explore tissue regeneration because the architecture and function are similar to humans and inbred genetic variants are available. Full‐ and partial‐thickness wounds were generated on the dorsum. Full‐thickness wounds at post‐wound day 57 exhibit severe scar with no signs of wound‐induced hair follicle neogenesis. Wound contraction is greater in the anterior/posterior relative to the medial/lateral axis. In wound beds, K14 + cells increased while K10 +, p63 + and PCNA + cells decreased compared to unwounded tissue. Epithelial β‐catenin is unchanged. The wound bed expresses more ColI, less ColIII and no elastin. Rete ridges do not form after full‐thickness wounding, but incompletely regenerate after partial‐thickness wounding. An alkaline phosphatase (ALP) + cell population, not associated with hair follicles, is present at the bottom of the rete ridge basal layer in pig and human unwounded skin. These K5 + /K10 − /PCNA − /ALP + epithelial cells are absent after full‐thickness wounding but reappear after partial‐thickness wounding, before invagination of new rete ridges. In summary, full‐thickness wounding on the dorsum of Lanyu pigs results in scar formation and perturbed molecular expression while partial‐thickness wounding permits limited rete ridge and papillary dermis regeneration. Future functional studies and further characterization will help contribute knowledge for the regenerative medicine field.